Exploring Anthropometric and Laboratory Differences in Children of Varying Ethnicities with Celiac Disease - Seema Rajani; Abeer Alzaben; Leanne Shirton; Rabindranath Persad; Hien Q Huynh; Diana R Mager; Justine M Turner (Canadian Journal of Gastroenterology and Hepatology)
BACKGROUND: Celiac disease (CD) is a common autoimmune disorder with an increasing prevalence, including in ethnic minorities.